2020
DOI: 10.1097/hjh.0000000000002283
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure dipping and sleep quality in the Wisconsin Sleep Cohort

Abstract: Aims: Nondipping blood pressure (BP) is associated with higher risk for hypertension and advanced target organ damage. Insomnia is the most common sleep complaint in the general population. We sought to investigate the association between sleep quality and insomnia and BP nondipping cross-sectionally and longitudinally in a large, community-based sample. Methods: A subset of the Wisconsin Sleep Cohort (n = 502 for cross-sectional analysis and n = 260 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…To the best of our knowledge, the findings of this study support some previous studies. [17][18][19] As a result of our study, we found that especially in ND and RD groups, there was increased sleep disturbance and insomnia and decreased sleep time.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…To the best of our knowledge, the findings of this study support some previous studies. [17][18][19] As a result of our study, we found that especially in ND and RD groups, there was increased sleep disturbance and insomnia and decreased sleep time.…”
Section: Discussionsupporting
confidence: 54%
“…22 In the study of Lyu et al evaluating 368 normotensive individuals between the ages of 30-60, it was found that clinical features of insomnia and poor sleep quality are associated with non-dipping BP. 18 In Lyu et al 's study using the Wisconsin Sleep Cohort, 18 polysomnography and ABPM readings of all participants were obtained at random intervals, every 15-20 minutes during wakefulness, and every 30 minutes during sleep. In our study, ABPM measurements were obtained during wakefulness and sleep every 30 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By utilizing 24-ABPM measurements and objective and subjective markers of insomnia, a separate study involving 502 participants aged 30-60 years from the Wisconsin sleep cohort documented significant cross-sectional associations of subjective and objective sleep quality markers with BP non-dipping (including both systolic and diastolic non-dipping). Additionally, the same study showed in longitudinal analyses that longer wake after sleep onset, longer total sleep time and lower sleep efficiency were associated with higher risk of systolic non-dipping 19 . In contrast, our study did not find differences in systolic dipping between older men with and without insomnia symptoms.…”
Section: Discussionmentioning
confidence: 80%